إسهام حفظ القران الكريم لترقية المهارة الكلام لطلاب الصف الثامن في معهد ابن عقيل الاسلامي الحديث - Khofifaturrochmah, Khofifaturrochmah; Rahmaini, Rahmaini (Jurnal Simki Pedagogia, 2024)
Memorizing the Al-Quran is one aspect that can be used in assessing Arabic language learning, one of which is speaking ability. This is because in memorizing the Al-Quran a person will get used to saying Arabic sentences, where Arabic is the language of choice in writing the Al-Quran. This research is field research, while the research approach is a quantitative approach, meaning that research design objectivity is carried out using statistical processing of numbers, structures and controlled experiments. Judging from the population and sample, this research data is a population sample research, because it involves all research subjects, namely class VIII. Data collection techniques used observation and interviews. The aim of this research was to determine the contribution of memorizing the Al-Quran to the speaking ability of students at Tahfiz Ibnu Aqil Islamic boarding school. From the results of the product moment correlation analysis, the correlation coefficient value of Arabic language ability with the ability to memorize the Al-Quran obtained a value of 0.602. This means that the relationship between Arabic language ability and the ability to memorize the Al-Quran is interpreted in the strong relationship category. So it can be concluded that in this study there is a positive relationship between the ability to memorize the Al-Quran and Arabic language ability.